Before ALL calculation, identify which operation it is!
Then follow the instructions for this operation.

Have the numbers SAME SIGN?
YES - Same signs
Find the SUM:
NO - Differnet signs:
Find theDIFFERENCE:
(-3) + (-6) = (-9)

(+4) + (+5) = (+9)
(+5) + (-7) = (-2)

(-4) + (+6) = (+2)

##### Always:   Keep the sign of the number with the GREATER absolute value.

 SUBSTRACTION

First, we must transform the SUBTRACTION into ADDITION;

### (-6) - (+2) =

 1. The first number remains the same. 2. Turn subtraction into addition. 3. Invert the sign of the second number 4. Follow the rules for addition. (-6) - (+2) = (-6) (-6) + (-6) + (-2) (-6) + (-2) = (-8) Substract means:       Add the opposit. (+2) - (-6) = (+2) + (+6) = (+8) Substract means:       Add the opposit. (-7) - (-3) = (-7) + (+3) = (-4) Substract means:       Add the opposit. (+4) - (+9) = (+4) + (-9) = (-5)

 MULTIPLICATION OR DIVISION

First, YOU MUST DO the multiplication or division.

Then we determine the sign:

We count the number of negative signs....

Do we have a EVEN number of negative signs?
 Yes AnEVEN number of négative sign the result is POSITIVE NO AnODD number of négative sign the result is NEGATIVE
 (-2) * (-4) * (-6) DO the multiplication or division, neglecting the signs: 2 * 4 * 6 = 48 Count the number of negative signs .... Determine the sign of the result: (-2) * (-4) * (-6) = Is there an EVEN number of negative signs? If YES , the result is POSITIVE otherwise, the result is negative In total THREE NEGATIVE SIGNS Three is ODD  . So the result is NEGATIVE -48

 (4) ÷ (2) * (6) = 12 In total ZERO NEGATIVE SIGNS ZERO IS EVEN . So the result is POSITIVE (4) ÷ (-2) * (6) = -12 In total ONE NEGATIVE SIGN One is ODD . So the result is NEGATIVE (-4) ÷ (2) * (-6) = 12 In total TWO NEGATIVE SIGNS TWO IS EVEN . So the result is POSITIVE